The decentralized management of international cooperation as an essential contribution to local and global development as part of the OD. The Ecuadorian experience - Mera Zambrano, Paola Alexandra; Papa, Ettore (Revista Española de Desarrollo y Cooperación, 2023)
This article highlights the need to deepen the local contributions to the debate on post-2015 development goals, stating some examples of successful processes of the Ecuadorian experience. Furthermore, reference is made to the importance of decentralized cooperation and to the need of taking advantage of local expertise to promote development on a global scale.
Keywords: Local development; Post-2015 Goals; Development cooperation; Decentralized cooperation; Ecuador